2016
DOI: 10.1016/j.rmed.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms/diseases prevalence is still increasing: a 25-yr population study

Abstract: While asthma and allergic rhinitis increasing trends were confirmed, with respect to other international studies, also a COPD increasing prevalence rates was shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 36 publications
(49 reference statements)
8
60
0
Order By: Relevance
“…However, its inclusion in the model did not decrease the effect of smoking habits on ALS outcome. The prevalence of COPD in our population is in keeping with recent epidemiological studies in the Italian population 26 27. In our cohort COPD was also found in never-smokers patients, though in a smaller percentage than in current and former smokers 28…”
Section: Discussionsupporting
confidence: 91%
“…However, its inclusion in the model did not decrease the effect of smoking habits on ALS outcome. The prevalence of COPD in our population is in keeping with recent epidemiological studies in the Italian population 26 27. In our cohort COPD was also found in never-smokers patients, though in a smaller percentage than in current and former smokers 28…”
Section: Discussionsupporting
confidence: 91%
“…In that Italian study, the increase in current asthma was observed mainly among subjects without a report of allergic rhinitis, which contrasts to our results. Another Italian study over 25 years also found an increase in asthma prevalence until 2011 . Results on asthma prevalence trends among adults are lacking for the time‐period after 2011, why our up‐to‐date results of an ongoing increase add important knowledge to this field.…”
Section: Discussionmentioning
confidence: 90%
“…Another Italian study over 25 years also found an increase in asthma prevalence until 2011. 48 Results on asthma prevalence trends among adults are lacking for the time-period after 2011, why our up-to-date results of an ongoing increase add important knowledge to this field.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies were also the basis to ascertain the overlap of asthma, chronic bronchitis and emphysema, with or without airflow obstruction, through a Proportional Venn Diagram [12]. At last, the very recent publication covering a 25-year span [13] has reported a definite increasing trend for all chronic obstructive respiratory symptoms / diseases, as well as for airflow obstruction, with the highest increments shown by allergic rhinitis, usual phlegm, COPD, and airflow obstruction.…”
Section: Epidemiology Of Obstructive Lung Disease and Adherence To Trmentioning
confidence: 99%